2022
DOI: 10.3390/f13071017
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus pellita Coppice vs. Seedlings as a Re-Establishment Method in South Sumatra, Indonesia

Abstract: Eucalyptus pellita can be regenerated through coppice. We report on the first known study of full-rotation productivity of E. pellita coppice and seedling re-establishment methods. We conducted this study at a high productivity site in South Sumatra, with the objectives to (1) evaluate the productivity of a first rotation of coppice stand in comparison with a replanted seedling crop, (2) investigate the effect of nitrogen (N) and phosphorus (P) fertiliser application on growth, and (3) examine the effect of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…While for the Acacia hybrid was 131 m 3 .ha -1 to 200 m 3 .ha -1 . The stand volume for E. pellita after 36 months in this study was lower than the study in South Sumatra reported by Hardiyanto et al [12] with approximately 75 m 3 .ha -1 . It shows that the appropriate site planting conditions are crucial for the growth of E. pellita [10].…”
Section: Stand Productivity and Energy Potentialcontrasting
confidence: 85%
“…While for the Acacia hybrid was 131 m 3 .ha -1 to 200 m 3 .ha -1 . The stand volume for E. pellita after 36 months in this study was lower than the study in South Sumatra reported by Hardiyanto et al [12] with approximately 75 m 3 .ha -1 . It shows that the appropriate site planting conditions are crucial for the growth of E. pellita [10].…”
Section: Stand Productivity and Energy Potentialcontrasting
confidence: 85%